PRICK AND SOAK Agroacterium tumefaciens-MEDIATED IN PLANTA TRANSFORMATION IN TOMATO (Lycopersicon esculentum Mill.) - I Putu Wahyu Sanjaya; Rindang Dwiyani; I Gede Putu Wirawan; Bambang Sugiharto (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2018)
One of the modern plant breedings through genetic engineering is Agrobacterium tumefaciens-mediated transformation. Agrobacterium tumefaciens-mediated transformation can be performed in vitro or in planta. In planta transformation arises from the weaknesses of the in vitro method such as need high hygiene standard, professional tissue culture experts, and more time to prepare explants and somaclonal variation. In planta transformation is a method to transfer the gene to the plant genome without any tissue culture stages. The aims of this research were to know the possibility of the prick and soak in planta method with the target of tomato seeds and to know the most suitable inoculation time for tomato seeds transformation by prick and soak method the transformation is done by pricking the seeds and soaking them in the A. tumefaciens suspension. The treatments in this study were 1 and 2 days inoculation time to test the efficacy of prick and soak in planta transformation method. Tomato seeds were pricked with a needle on the center once, and then soaked in A. tumefaciens strain LB4404 suspension carrying pKYS-SoSPS1 plasmid with Neomycin Phosphotransferase (NPTII) and Saccharum officinarum Sucrose Phosphate synthase (SoSPS1) genes. Visualization of tomato’s DNA samples after PCR showed that 1-day inoculation sample was positively integrated with NPTII gene and negative in the 2 days inoculation treatment.